Reconnaissance politique des savoirs professionnels - Jessica Thomas (Revue d'anthropologie des connaissances)
This paper combines an anthropology of knowledge and a sociology of public policy, in order to analyze the impacts of public support provided to a group of French farmers to promote production and formalization of knowledge activities. Balancing these two approaches helps to understand the convergence of professional and institutional aspirations in experimentations led by farmers aiming to improve the environmental impact of their agricultural practices. The group of farmers received a public subsidy to experiment with the agroecological practices of direct seeding, within the framework of the “agroecological transition policy”, launched by the French ministry of agriculture in 2012.The purpose of the study presented in this paper is to analyze the impact of institutional acknowledgement of professional knowledge towards more ecological farming practices. Four structuring effects of the political acknowledgment of professional knowledge on the group’s activity are presented: firstly, the discourse on the relevance of professional knowledge is a driving force for the group members to start experimenting. Second, the acknowledgement of professional knowledge allows this group to warrant its positioning in the local agricultural landscape, especially to enhance their credibly in front of public authorities. Thirdly, the farmers in the studied group develop a reflexivity on their profession as a consequence of the valorisation of farmers’ knowledge. Finally, there are organizational consequences for this group of farmers, as a result of their intention to reappropriate their own decisions to themselves. By claiming their capacity to build a “collective expertise” and through their defense of an “expert-farmer” status, the members of the group, influenced by a context of better valorisation of their knowledge, act, think and organize themselves with the objective of a self-appropriation of their decision, in a way that is specific to them.